Analisis Pengaruh Ideologi Terhadap Nasionalisme Warga Negara - Safaruddin Safaruddin; Yelli Aswariningsih; Ibnu Sodik; Hema Malini (MAN 4 Kota Pekanbaru, 2026)
This study aims to examine the influence of state ideology on citizen nationalism. The research employed a quantitative approach using a correlational method to analyze the relationship between ideology as the independent variable and nationalism as the dependent variable. Data were collected through research instruments that had passed validity and reliability testing, and were analyzed using the product-moment correlation technique. The results showed that state ideology has a strong and significant influence on citizen nationalism, with a correlation coefficient indicating a high level of relationship between the two variables. The coefficient of determination shows that ideology contributes substantially to the formation of citizen nationalism, while the remaining influence is affected by other factors not examined in this study. These findings indicate that strengthening the understanding and internalization of state ideology is an important strategy to enhance citizen nationalism in the era of globalization.